Alongshore Variable Accretional and Erosional Coastal Foredune Dynamics at Event to Interannual Timescales. Issue 12 (7th December 2022) - Cohn, Nicholas; Brodie, Katherine; Conery, Ian; Spore, Nicholas
Abstract: Natural and constructed dunes are increasingly being utilized to buffer flooding impacts from storms and rising sea levels along sandy coastlines. However, a lack of data at the appropriate spatial and temporal resolution often precludes isolating the total magnitude, specific timing, and alongshore variability of volumetric coastal dune changes resulting from both wave and wind‐driven processes. Here mobile terrestrial lidar data from 46 collections along a 6.5 km stretch of sandy beach and dunes in Duck, NC, USA are used to assess the magnitude and drivers of alongshore variable dune responses between 2012 and 2020. Despite numerous major storm events which impacted the dunes over this time period, the dunes grew volumetrically both in nourished and un‐nourished sections of the study site. Growth of the dunes was seasonally and spatially variable with the largest total growth recorded in the Fall, coinciding with a period of frequent windy storms but also the highest total water levels, and along the regions with the lowest gradient β beach . The vertical accretion patterns of these wind‐blown sediments are shown to vary depending on the dune management style, specifically, if dunes were not managed, sand fenced, or artificially constructed. Dune erosion also occurred episodically within the study period, with the steepest sloped beach sections likely to be the most impacted during individual storm events. Key Points: Both wind and wave‐driven contributions to volumetric dune change are measurable at event scale using mobile terrestrial lidar The fastest dune growth rates are generally on sections of coast with the mildest beach slopes Anthropogenic activities, including nourishment and sand fencing, have a quantifiable effect on the magnitude and style of dune evolution